(untitled) (Journal of the Management Sciences, 2023)
Undue political interference on the smooth running of publicly owed media organizations leading to gross inefficiency has been a monster very difficult to tame. This paper therefore examines the effect of political interference and efficiency of public sector in Nigeria: a study of Broadcasting Service of Ekiti State. It examines the level of political interference leading to inefficiency in Broadcasting Service of Ekiti State, investigates ways politicians interfere in Broadcasting Service of Ekiti State that leads to inefficiency and identifies ways of reducing political interference in the public sector for efficient service delivery. It employs primary data analyses drawn from structured questionnaires issued to workers in Broadcasting Service of Ekiti State. To draw out representative sample size, the researcher purposively chose the entire 200 full employees of Broadcasting Service of Ekiti State from management, senior and junior staff levels. The study found that the level of political interference in the activities of Broadcasting Service of Ekiti State is high which is coursing inefficiency in the outfit. The paper therefore recommends among other things that appointment of politicians into top management positions in the media house should stop rather professionals with rich experience should be appointed for efficient service delivery. It is also recommended that National Broadcasting Commission should intensify their monitoring on the activities of publicly owned media houses and sanction all the erring media organisations.